Distributed Sensor Networks - Brooks, R.R. (CRC Press, 2009)
The vision of researchers to create smart environments through the deployment of thousands of sensors, each with a short range wireless communications channel and capable of detecting ambient conditions such as temperature, movement, sound, light, or the presence of certain objects is becoming a reality. With the emergence of high-speed networks and with their increased computational capabilities, Distributed Sensor Networks (DSN) have a wide range of real-time applications in aerospace, automation, defense, medical imaging, robotics, and weather prediction. Over the past several years, scientists, engineers, and researchers in a multitude of disciplines have been clamoring for more detailed information without much success. Until now, in fact, this evolving technology was so new and proprietary that information has been available only in scattered articles or basic books.